Nonlinear optical absorption of Co3(PO4)2·4H2O nanosheets in broadband spectra. (20th October 2022) - Wang, Chang; Duan, Ran; Xiao, Xingcheng; Wang, Yingwei; Chen, Zhihui; Li, Yejun; Xiao, Si; He, Jun
Abstract: Long hexagonal Co3 (PO4 )2 ·4H2 O nanosheets were synthesized using a hydrothermal method, where their nonlinearity was probed via a femtosecond Z-scan system. The results show that the Co3 (PO4 )2 ·4H2 O nanosheets exhibit saturable absorption when the incident photon energy is greater than the forbidden band width, while optical limiting is found when the incident photon energy is smaller than the forbidden band width. In particular, the obtained Co3 (PO4 )2 ·4H2 O nanosheets demonstrate the best optical limiting properties at 600 nm. The present study suggests the cobalt phosphates nanosheets as a promising candidate for optical limiters.